PEMBERDAYAAN MASYARAKAT MELALUI SOSIALISASI PROGRAM PENCEGAHAN STUNTING DI KELURAHAN BENDUNG KECAMATAN KASEMEN KOTA SERANG - Ihwan Satria Lesmana; M. Ali Nurdin; Hani Rahayu; Nur Sita; Husni Kamil; Rosye Nurindah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Student Work Lecture (KKM) is a concrete manifestation of the responsibilities of lecturers and students in carrying out the Tri Darma of Higher Education, which includes education, research, and community service. Through this platform, students are able to apply their knowledge directly to members of the community in Bendung Village. One form of service implemented by students is to provide understanding to the community in Bendung Village, Kasemen District, Serang City, regarding the issue of stunting. Stunting refers to a state of growth failure that occurs in children under five due to chronic lack of nutrition, causing children to be shorter than their normal height for their age. This condition generally occurs in the first 1000 days of life (HPK), which is an important period in a child's development. In an effort to disseminate information regarding stunting prevention, the observation method is the approach taken. Students and health workers went directly to the field to see in depth the environmental and health conditions in the people of Bendung Village, Kasemen District. Concrete steps taken by students and lecturers in the KKM not only provide direct benefits to society, but also inspire a sense of social responsibility among students. Education and awareness are powerful tools in addressing public health challenges such as stunting, and this initiative is a positive step towards creating a healthier future for children in Kelurahan Bendung